The Effects of Heel Height on Postural Stability of Healthy Young Females - Ebrahim Sadeghi-Demneh; Ladan Arab-Yaqoubi (Vesnu Publications, 2015)
Introduction: High heel shoes alter the kinematics and muscle activity patterns of the lower extremities and spine. These changes in biomechanical characteristics of the body could be a challenging issue for postural stability system. The objective of this study was to investigate the effects of different heel heights on the postural sway of healthy young women. Materials and Methods: Thirty-two female students who aged 22.3 ± 1.4 year old volunteered in this randomized cross-over trial. The center of pressure parameters were recorded while participants stood upright on a forceplate in four random conditions: barefoot, with zero heel-height shoes, with 3 cm heel-height shoes, and with 6 cm heel-height shoes. The recoded data was statistically analyzed using repeated measures ANOVA. Results: The statistical analyses indicated significant differences between the different heel heights (P < 0.050). The raising of heel height caused increases in the mean velocity F(3,29) = 4.6; P < 0.015, path length F(3,29) = 23; P < 0.001, and the range F(3,29) = 23; P < 0.001 of the body sway in different conditions of this study. Conclusion: It seems that increasing in heel height caused some alteration in the boy sway parameters which could induce a postural instability.